Perennial Cotton Ratoon Cultivation: A Sustainable Method for Cotton Production and Breeding - Zhang, Xin; Yang, Qian; Zhou, Ruiyang; Zheng, Jie; Feng, Yan; Zhang, Baohong; Jia, Yinhua; Du, Xiongming; Khan, Aziz; Zhang, Zhiyong (Frontiers in Plant Science, 2022)
Cotton production is challenged by high cost with multiple management and material inputs including seed, pesticide and fertilizer application. The production costs can be decreased and profits can be increased by developing efficient crop management strategies, including perennial cotton ratoon cultivation. This review focuses on the role of ratoon cultivation in cotton productivity and breeding. In areas that are frost free throughout the year, when the soil temperature is suitable for cultivation in spring, the buds of surviving cotton plants begin to sprout so their flowering and fruiting periods are approximately 4-6 weeks earlier than those of sown cotton. Due to the absence of frost damage, the ratoon cotton continues to grow , and the renewed plants can offer higher yield than cotton sown in the following season. Moreover, no-tillage cultivation from the first ratoon without sowing can help conserve seeds, reduce labor inputs, and reduce soil and water loss. In this review, the preservation of perennial cotton germplasm resources, the classification and genome assignment of perennial species in the cotton gene pool, and effective strategies for the collection, preservation, identification and utilization of perennial cotton germplasms are discussed. Ratoon cultivation is the main driver of cotton production and breeding, especially to maintain male sterility for the utilization and fixation of heterosis. Ratoon cultivation of cotton is worth adopting because it has succeeded in Brazil, China, and India. Therefore, taking advantage of the warm environment to exploit the indeterminant growth habits of perennial cotton for breeding would be an efficiency-increasing, cost-saving, and eco-friendly approach in frost-free regions. In the future, more attention should be given to ratooning perennial cotton for breeding male sterile lines.